Analysis Translation Technique of Short Story "The Necklace” By Guy De Maupassant - Arrosyid, Rofingudin; Setiawan, Teguh; Siregar, Try Mahendra (International Journal of Contemporary Studies in Education, 2024)
This research aims to analyze the translation strategy used in the short story The Necklace (Harga Sebuah Kalung) written by Guy De Maupasant and translated by Syafruddin Hasani. This study uses a qualitative descriptive research method. From the results of the analysis it is known that the translation techniques used by the translator in translating the short story Necklace (The Price of a Necklace) by Guy De Maupasant are the compensation technique with 99 data, the literal translation technique with 24 data, the linguistic amplification technique with 17 data, the reduction technique with 7 data , calque with 7 data, the discursive creation technique with 3 data, the discursive creation technique with 3 data. particularization with 2 data, modulation with 2 data, variation technique with one data, adaptation with one data, generalization with one data and establishment equivalent with one data.